Pengaruh Peran Kepemimpinan Demokratis Kepala Sekolah, Komunikasi Interpersonal, Motivasi Kerja Guru terhadap Kinerja Guru BK - Vapea Pinta Lahi Tobing; Rosnelli Rosnelli; Joharis Lubis (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
This study aims to analyze the direct effects of several variables as follows: the democratic leadership style of school principals on work motivation; interpersonal communication on work motivation; the democratic leadership style of school principals on the performance of guidance and counseling teachers; interpersonal communication on the performance of guidance and counseling teachers; and work motivation on the performance of guidance and counseling teachers. The population of this study includes 55 guidance and counseling teachers working in public vocational high schools in Deli Serdang Regency. Based on calculations using the Slovin formula, a sample of 35 individuals was obtained through random sampling methods. Data collection was conducted through instrument trials, showing very high reliability: democratic leadership of school principals: 0.807; interpersonal communication 0.825; work motivation 0.810; and performance of guidance and counseling teachers 0.807. This research employs path analysis to gather information related to the study and test the relevant theories. The results of hypothesis testing indicate that the democratic leadership style of school principals, interpersonal communication, and work motivation have a positive influence on the performance of guidance and counseling teachers.